Evaluasi Pelaporan Keuangan Entitas Nirlaba (Studi Kasus: Yayasan Garuda Nusantara Karangawen Demak) - Prasetyo, Dwanda Alde; Firmansyah, Amrie (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
This study aims to review the implementation of accounting for non-profit organizations. This research method uses a qualitative descriptive approach. This study uses a case study of Garuda Nusantara Foundation in Karangawen, Demak. The evaluation conducted in this study includes the practice of applying accounting for non-profit entities and comparing with the Indonesia Statement of Financial Accounting Standards (SFAS) No 45.The study was conducted during the March-May 2018 period. Interviews with informants were carried out in the first week of May 2018. The informants in this study was a financial manager of the Foundation. The items of questions asked are related to the types of financial statements prepared, the accounting policies that apply in the preparation of financial statements, the procedures for preparing financial statements.The result suggests that the financial statements prepared by the Foundation are still not in accordance with the standards set out in Indonesia SFAS No. 45. The Foundation does not follow the standards or guidelines for the preparation of any financial statements and only prepare income statements and balance sheets that are not in accordance with the standards financial statements of non-profit entities regulated in Indonesia SFAS No. 45. In addition, financial staff still do not have the knowledge of the preparation of financial statements in accordance with Indonesia SFAS No 45 and only follow the form of financial reports that have been made since the foundation was established.